UNDERSTANDING THE DYNAMICS OF HYPERINFLATION IN DEVELOPING ECONOMIES - Biradar, Shravanakumari S (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Understanding the dynamics of hyperinflation in developing economies requires a comprehensive analysis of the complex interplay of economic, political, and social factors that contribute to its emergence and escalation. Hyperinflation occurs when a country's inflation rate reaches exceptionally high levels, often driven by unsustainable government debt, currency devaluation, and loss of public confidence in the monetary system. In developing economies, where institutions may be weak and governance structures vulnerable, the likelihood of hyperinflation is amplified. One key factor contributing to hyperinflation in developing countries is excessive government borrowing, often to finance large deficits or respond to political crises. This borrowing is frequently monetized by printing more money, which increases the money supply without a corresponding increase in goods and services, leading to inflation. Coupled with external shocks such as natural disasters, commodity price fluctuations, or geopolitical tensions, the economy can spiral into hyperinflation. Political instability and governance failures also play a pivotal role in triggering hyperinflation. In many developing nations, governments may resort to money printing as a quick fix to fiscal imbalances, undermining the credibility of the currency. The lack of effective monetary policy, transparency, and accountability in these economies exacerbates inflationary pressures. Additionally, the collapse of trust in the national currency often results in the adoption of foreign currencies, further destabilizing the domestic economy. The socio-economic impact of hyperinflation is profound, as it erodes savings, disrupts trade, and deepens poverty. Hyperinflation also results in social unrest and political instability, with long-term consequences for development. Understanding these dynamics is critical for policymakers and international organizations seeking to prevent or mitigate the occurrence of hyperinflation and its detrimental effects in developing economies. Keywords: Understand, Dynamics, Hyperinflation, Developing Economies.